A Perceptual Method to Rate Dysphonic Voices - Gurlekian, Jorge Alberto (2017)
ObjectiveTo present and test a production-matching method with external references, looking at the improvement of inter-rater variability of expert evaluations.MethodIt consists of adjusting quality attribute levels of a synthetic vowel for a simultaneous matching with the natural patient vowel (NPV) attributes. In an initial experiment, seven speech-language pathology (SLP) experts performed this task with the new method and evaluated the same NPV with the standard method. Targets were twelve NPVs with a variety of quality attribute combinations. In a second experiment, we employed the proposed method to assess the evaluation performance of 65 SLP students.ResultsExpert evaluations show less dispersion for the proposed method than those obtained using the standard rating method. Student individual responses were compared with overall responses from their own group and were cross referenced with expert responses. A Kappa index is proposed as a measure of SLP students´ performance.ConclusionsThe proposed method was readily accepted by both SLP experts and students. Experts´ consensus was improved. SLP students could benefit by quickly learning to discriminate complex attributes, which usually demands demands years of experience.Key WordsDysphonic voice; Evaluation; Production; Matching; Inter-rater variability